From Near and Afar: International Secondary School Students' Career Influences. (April 2023) - Arthur, Nancy; Lei, Danni; Woodend, Jon
During the previous decade, growth in the numbers of internationally mobile students included international high school students. Prior research on international students' career development in higher education may not account for the unique context of younger international students in secondary schools. The current study investigated career influences for international secondary students, using the Systems Theory Framework (Patton & McMahon, 2021 ). International students in senior years completed written, open-ended surveys and in-person interviews regarding their career aspirations, plans and key influences on their decision-making. International student coordinators and school staff also offered their perspectives about these influences. Results indicate the inter-related systemic influences of individuals, significant relationships, location and country contexts, the secondary school environment, and perceived characteristics of occupations and future career pathways. Implications for supporting international high school students in the school setting and future research directions are discussed.